Analysis of Mathematical Problem About Mathematics Students in Class Xi and Self-Efficacy Learning in 7e-Learning Cycle - Swasono, Andi Hepi; Kartono, Kartono; Rochmad, Rochmad (Universitas Negeri Semarang, 2018)
This study aimed to testing and analyze the effectiveness of the 7E-learning cycle learning model on the derived function learning. The research design used was a combination of qualitative and quantitative methods, also known as mixed methods. The model combines quantitative and qualitative methods unbalanced and in one time. Then do the overall interpretation of data analysis to get a conclusion and suggestions. Quantitative research in phase 2, the research used is experimental research using quasi-experimental designs. The researcher chose quasi-experimental designs with non-equivalent control group design. This study there are two groups selected at random. The first group was the experimental group where the 7E-learning cycle was implemented and the second group was the control group received no special treatment or regular treatment. Based on the research results obtained conclusion as learning Cycle 7E model of learning quality to solving problems of class XI students in solving problem solving problems included in either category.